ENT 530 Business Plan / Mohamad Alzafri Mohd Haniza ... [et al.] - Mohd Haniza, Mohamad Alzafri; Mohd Hamezan, Muhammad Amir Fahmi; Mohd Azhari, Muhammad Amir Syahmi; Murad, Muhammad Ammar Naim; Mohd Zahari, Muhammad Azri Syazwan (2019)
Mon Ami Sdn Bhd is a brand new company that will be emerge as a company that innovate classic snacks to a new creative approach. Mon Ami Sdn Bhd has the meaning of "Friends" in France which represents our excellence teamwork to innovate the snacks into something that unique for the market.